Phenotypic Characterization and Antibiotics Combination Approach to Control the Methicillin-resistant Staphylococcus aureus (MRSA) Strains Isolated from the Hospital Derived Fomites - Pravin R Dudhagara (Asian Journal of Medical Sciences, 2011)
Objective: The emergence of antibiotic resistant Stphylococcus aureus strains have resulted in significant treatment difficulties which have imposed a burden on health care systems and simultaneously intensifying the need for new antimicrobial agents. Therefore, we have designed the study to determine the prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) and their antimicrobial susceptibility pattern along with evaluation of antibiotic combination approach.